Treatment of subclavian steal syndrome with percutaneous transluminal angioplasty and stenting: case report - Felipe Fregni; Luiz Eduardo Coutinho Castelo-Branco; Adriana Bastos Conforto; Fabio Iuji Yamamoto; Cynthia Resende Campos; Paulo Puglia Jr.; José Guilherme Mendes Pereira Caldas; Milberto Scaff (Arquivos de Neuro-Psiquiatria)
Subclavian steal syndrome refers to the association of neurological symptoms related to vertebrobasilar insufficiency and the phenomenon of subclavian steal. We report the case of a 63 year-old male patient that presented subclavian steal syndrome and severe proximal (80%) stenosis of the left subclavian artery. The patient was submitted to percutaneous transluminal angioplasty and stenting on the left SA. The procedure was well tolerated and immediately afterwards, there was complete remission of the symptoms and of the phenomenon of subclavian steal evaluated by angiography and transcranial doppler. We propose that percutaneous transluminal angioplasty with stenting placement is a good therapeutic option for subclavian steal syndrome.